Safely Increasing Connection to Community-Based Services: A Study of Multidisciplinary Team Decision Making for Child Welfare Referrals. (August 2022) - Chambers, Jaclyn E.; Roscoe, Joseph N.; Berrick, Jill Duerr; Lery, Bridgette; Thompson, Doug
Initial child welfare screening decisions, traditionally made by an individual worker, determine if a family will receive further intervention by child protective services. A multi-disciplinary team (MDT) decision-making approach for child welfare referrals aims to provide a more thorough assessment of needs and strengths and to connect families to appropriate community-based providers. This study examined 159 child welfare referrals handled by MDTs compared to 331 referrals handled via the traditional screening approach. The study used a pseudo randomization procedure to assign referrals to the study conditions: Referrals logged on 2.5 days of the week were assigned to the treatment group; all others were assigned to the comparison group. Referrals handled by an MDT were more than four times as likely as those not handled by an MDT to be referred to community-based organizations ( OR = 4.32, p < .001). There were no statistically significant differences in families' engagement with community-based organizations or child welfare outcomes. MDTs are a promising step in the initial process of connecting families to services, although they did not affect this study's longer-term outcomes.